Теоретико-методологічні засади діагностичного прогнозування рівнів споживання електричної енергії підземними залізорудними підприємствами - Сінчук, Олег Миколайович; Сінчук, Ігор Олегович (НТУ "ХПІ", 2019)
Гірничорудні підприємства являють собою зразок найбільш енергоємних видів підприємств, що впливає на загальний показник собівартості видобутку деяких видів корисних копалин. Запропонована методологія діагностики реальних рівнів споживання електроенергії на підприємствах з підземними способами видобутку залізної руди. Науковий підхід запропонований у статті щодо формування методологічних засад оцінки та діагностичного прогнозування споживання електроенергії дозволяє виділити систему принципів, яка має інноваційні елементи.

The article states that mining enterprises, including their subspecies – ore mining, represent an example of the most energy-intensive types of enterprises. The level of electricity efficiency of these types of enterprises – the main economic impact on the total cost of production of certain types of minerals. The methodology of diagnostics of real levels of electricity consumption at a number of mining enterprises of Ukraine with underground mining of iron ore (iron raw materials) is proposed. The analysis allowed to assess the parameters of the electric power industry of the iron ore enterprises as a whole and to allocate a line of the most energy-intensive consumers of electric energy. It is noted that existing methods of assessing the levels of electricity consumption of the analyzed types of enterprises do not meet the modern requirements, the purpose of which is a concrete forecast of the expected levels of electricity consumption, with the purpose of the current control of this process in the function of change of technological conditions for the extraction of iron ore raw materials. The scheme of solving the task is proposed: identification of the real state of electricity consumption; detecting changes in consumption levels in a spatial-temporal section; establishment of the main factors causing changes in energy consumption; accounting of levels of their influence on the process of electricity consumption. Forecast of consumption levels – system assessment of the effectiveness of management of levels of electricity consumption in the function of daily tariffs. The scientific approach proposed inthe article on the formation of methodological principles of diagnostic forecasting of electricity consumption allows to identify a certain system of principles that has synergetic innovation elements.
Theoretical and methodological substances of diagnostic prognosis of electric power consumption levels of underground iron ore enterprises
Keywords: визначення факторів впливу; електрична енергія; прогноз; залізорудна сировина; electric energy; forecast